Clinical practice models in nursing education: implication for students' mobility. (5th January 2015) - Dobrowolska, B.; McGonagle, I.; Jackson, C.; Kane, R.; Cabrera, E.; Cooney‐Miner, D.; Di Cara, V.; Pajnkihar, M.; Prlić, N.; Sigurdardottir, A.K.; Kekuš, D.; Wells, J.; et al.
<x xml:space="preserve">Abstract</x> Background In accordance with the process of nursing globalization, issues related to the increasing national and international mobility of student and qualified nurses are currently being debated. Identifying international differences and comparing similarities for mutual understanding, development and better harmonization of clinical training of undergraduate nursing students is recommended. Aims The aim of the study was to describe and compare the nature of the nursing clinical practice education models adopted in different countries. Methods A qualitative approach involving an expert panel of nurses was adopted. The Nominal Group Technique was employed to develop the initial research instrument for data collection. Eleven members of the UDINE‐C network, representing institutions engaged in the process of professional nursing education and research (universities, high schools and clinical institutes), participated. Three data collection rounds were implemented. An analysis of the findings was performed, assuring rigour. Results Differences and homogeneity are reported and discussed regarding: (a) the clinical learning requirements across countries; (b) the prerequisites and clinical learning process patterns; and (c) the progress and final evaluation of the competencies achieved. Conclusions A wider discussion is needed regarding nursing student exchange and internalization of clinical education in placements across European and non‐European countries. A clear strategy for nursing education accreditation and harmonization of patterns of organization of clinical training at placements, as well as strategies of student assessment during this training, are recommended. There is also a need to develop international ethical guidelines for undergraduate nursing students gaining international experience.